Modelling firm (re-)location choice in UrbanSim - Balz R. Bodenmann (European Regional Science Association (ERSA), 2011)
Over the last decade, low economic growth rates resulted in intensified competition between nations, regions, and towns in trying to attract new firms and inhabitants. In particular, the establishment of new firms has become one of the most vital objectives of governments and public authorities all over Europe. To raise the attractiveness of a region, different instruments have been used: tax reductions, incentives for new establishments, as business destination promotion activities, supply of outstanding infrastructure and public services. On the one hand, this paper investigates effects of different possible options for cantonal and municipal authorities' intent to attract firms: improvements in transport infrastructure, designation of new building zones, and last but not least tax reductions. These actions have been tested by simulating the decisions of existing firms. The parameters for these simulations have been estimated with a discrete choice model using data of the cantons St.Gallen and both Appenzell as well as Zurich. On the other hand, the paper aims to provide an approach to implement these models in UrbanSim. UrbanSim is a software-based simulation system for supporting planning and analysis of urban development, incorporating the interactions between land use, transportation, the economy, and the environment. At the moment, UrbanSim is adapted to an European context (see the according research project SustainCity, www.sustaincity.eu).
Keywords: 330